Modelling the Global Prevalence of COVID-19: An Econometric Approach - Adekunle, Wasiu; Oyolola, Feyisayo; Atolagbe, Oluwafemi; Abdulbasit, Ademola; Odugbemi, Taiwo; Ashiru, Yusuff (Growth, 2021)
Nearly all economies of the world suffered from the sudden outbreak of the coronavirus pandemic emanating from Wuhan City of China to the rest of the world. A number of studies have been conducted to investigate the drivers of the spread of the viral infection. We differ from existing studies by employing a cross-sectional quantile regression approach to uncover socio-economic conditions that are instrumental in the spread of COVID-19 in Africa, Asia, America and Europe. Across the continents, we observed that life expectancy, the size of the aged population and spending on the health sector have significant impacts on the spread of COVID-19. We also noted the specific roles of out-of-pocket spending, net migration and tourism attraction for Africa, America and Europe, respectively, in driving the viral spread. We therefore draw policy implications in terms of the need for improved spending on health sector across continents and the need to intensify health checks for travelers and immigrants, and also the need to emphasize regular check-ups for all individuals across continents since current realities have shown that no age-group is spared of contracting the viral infection.